2003
DOI: 10.1073/pnas.0438007100
|View full text |Cite
|
Sign up to set email alerts
|

The FKBP-associated protein FAP48 is an antiproliferative molecule and a player in T cell activation that increases IL2 synthesis

Abstract: FAP48 was identified and cloned thanks to its interaction with FK506-binding proteins (FKBPs) such as FKBP52 and FKBP12, which belong to the large family of immunophilins that bind the macrolide immunosuppressant drugs FK506 and rapamycin. We have previously shown that FAP48 -FKBP complexes are dissociated by FK506 and rapamycin, suggesting that FAP48 is an endogenous ligand of FKBP. The present work describes the biochemical consequences of FAP48 overexpression, induced by the tetracycline analogue doxycyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Additionally, KLF2 increases IL-2 expression. Similar results were shown with FK506-binding proteinassociated protein FAP48, which not only inhibits Jurkat T cell proliferation, but also increases IL-2 synthesis in PHA/PMA-activated Jurkat T cells (35). KLF2 appears to act similarly to FK506-binding protein in T cell activation.…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, KLF2 increases IL-2 expression. Similar results were shown with FK506-binding proteinassociated protein FAP48, which not only inhibits Jurkat T cell proliferation, but also increases IL-2 synthesis in PHA/PMA-activated Jurkat T cells (35). KLF2 appears to act similarly to FK506-binding protein in T cell activation.…”
Section: Discussionsupporting
confidence: 70%
“…The initial analysis of AtFIP37 protein sequence indicated a weak identity (20%) with FAP48, a mammalian FKBP12 and FKBP59-associated protein (Chambraud et al, 1996), which has an antiproliferative action and plays a role in T cell activation (Krummrei et al, 2003). Recently, we observed that two animal proteins, HsWTAP and DmFL(2)D, were found to share stronger identities with AtFIP37 (Fig.…”
Section: Atfip37 Is Homologous To Mammalian Proteins Involved In Splimentioning
confidence: 99%
“…FAP 48 (FKBP-associated protein, 48 kDa) is essential for normal development of the vascular system and has an antiproliferative effect on Daisy T cells [40]. The candidate tumor suppressor gene MXI1 (Max-interacting protein 1) negatively regulates Myc oncoprotein activity and is upregulated by overexpression of FAP48 [40].…”
Section: Erythropoietic Differentiationmentioning
confidence: 99%
“…During erythropoietic differentiation, genes associated with the proto-oncogene c-myc are continuously downregulated, including Mina53 (myc-induced nuclear antigen with a molecular mass of 53 kDa), which is involved in cell proliferation and is directly induced by c-myc [38,39]. FAP 48 (FKBP-associated protein, 48 kDa) is essential for normal development of the vascular system and has an antiproliferative effect on Daisy T cells [40]. The candidate tumor suppressor gene MXI1 (Max-interacting protein 1) negatively regulates Myc oncoprotein activity and is upregulated by overexpression of FAP48 [40].…”
Section: Erythropoietic Differentiationmentioning
confidence: 99%